Semaglutide treatment reverses HFD induced hippocampal microglia activation and improves cognitive dysfunction - Haodong Gong; Junlu Liu; Yihan Wang; Xufan Lin; Guangsen Wu; Yichao Ou; Mingfeng Zhou; le Yang; Junxiang Peng; Xinyun Ye; Yongjia Wang; Fei Xu; et al. (Tissue and Cell, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

SAIR reconstruction method based on deep generalized unfolding network - Xiaocheng Yang; Zihan Hou; Weihao Cheng; Jingye Yan; Lin Wu; Mingfeng Jiang; Bo Wei (Advances in Space Research, 2026)

Metabolic profiling of triptophenolide in rat plasma, urine, bile and faeces after intragastric administration - Mingfeng Jiang; Qiang Hou; Shuilian Wu; Xiaofan He; Tingting Zhang; Rongjing Zhou (Natural Product Research, 2025)

Multivariate data analysis of a severe air pollution event in Shihezi city, China - Feifan Chen; Qing He; Zhujun Zhao; Zhongqi Lu; Mingfeng Yang; Gang Ren; Jin Wang; Hongwei Zhang; Dongliang An; Chunxia Wu (Atmospheric Pollution Research, 2025)

Examining how green space patterns affect noise distribution in urban areas with varying built-up densities - Mingfeng Zhang; Yuanxiang Wu; Mengmeng Li; Qi Meng; Jian Kang (Journal of Environmental Management, 2025)

IRBITs, signaling molecules of great functional diversity - Ying Liu; Xuhui Feng; Han Wu; Tianxiang Gui; Mingfeng Fu; Xudong Luo; Lei Zhao; Li-Ming Chen (Pflügers Archiv - European Journal of Physiology, 2025)

Optimizing chemical topping in cotton: Effects of planting density and variety sensitivity to mepiquat chloride - Yanqin Wu; Chaoyuan Tang; Mingwei Du; Jingshan Tian; Mingfeng Yang; Yali Zhang; Wangfeng Zhang (Field Crops Research, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Multi-UAV reconnaissance mission planning via deep reinforcement learning with simulated annealing - Mingfeng Fan; Huan Liu; Guohua Wu; Aldy Gunawan; Guillaume Sartoretti (Swarm and Evolutionary Computation, 2025)

Promotion mechanism of rare-earth elements doping on performance of CaO/CeO2 sorbent for high temperature CO2 capture - Yunfeng Li; Jiarui Wu; Feng Liu; Weiwei Liu; Bin Li; Qingfa Zhang; Mingfeng Wang; Haiping Yang; Zhen Fang; Zhong Ma (Chemical Engineering Journal, 2025)

Cellulose-based photo-curable chiral nematic ink for direct-ink-writing 3D printing - Mingfeng Wu; Huan Wang; Afroza Akter Liza; Lukuan Guo; Wenyuan Zhu; Junlong Song; Fengshan Zhang; Yanshao Liu; Yongcan Jin; Jiaqi Guo (Carbohydrate Polymers, 2025)

Comparative study of failure mechanism of CFRP partially confined normal strength concrete (NSC) and UHPC cylinders under axial compression - Wanye Li; Yao Lu; Meizhong Wu; Peng Wang; Weiwen Li; Xingquan Wang; Mingfeng Kai; Jing Yu (Engineering Structures, 2025)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Polyoxometalate-mediated film bearing near-infrared photothermal self-healing property for seawater desalination - Shuangyu Wu; Dongdong Li; Mingfeng Wei; Bao Li; Lixin Wu (Chemical Engineering Journal, 2024)

Influence of climate and land use on watershed anthropogenic phosphorus inputs and riverine phosphorus export dynamics: A global analysis - Hao Wu; Xinyi Jiao; Yucang Wang; Mingfeng Wang; Jia Zhou; Kaibin Wu; Dingjiang Chen (Science of The Total Environment, 2024)

Separation of spring viraemia of carp virus from large-volume samples using immunomagnetic beads - Jing Hongli; Zhang Min; Gao Longying; Si Liegang; Wang Na; Ge Mingfeng; Xu Shengwei; Wang Jianping; Wu Shaoqiang (Archives of Virology, 2024)

Evaluation of three prevalent global riverine nutrient transport models - Xinyi Jiao; Jia Zhou; Minpeng Hu; Mingfeng Wang; Hao Wu; Kaibin Wu; Dingjiang Chen (Environmental Science and Pollution Research, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Small outbursts into big disasters: Earthquakes exacerbate climate-driven cascade processes of the glacial lakes failure in the Himalayas - Ningsheng Chen; Mei Liu; Simon Allen; Mingfeng Deng; Narendra Raj Khanal; Taixin Peng; Shufeng Tian; Christian Huggel; Kanglin Wu; Mahfuzur Rahman; Marcelo Somos-Valenzuela (Geomorphology, 2023)

Behaviour of electroosmotic consolidation by electrode configuration and fracture grouting - Yunguo Du; Chao Zhang; Changfei Gou; Wenwen Wu; Xiaobing Li; Xiuqing Hu; Wang Chaoliang; Li Mingfeng (Marine Georesources & Geotechnology, 2022)

Behaviour of thick marine deposits subjected to vacuum combined with surcharge preloading - Dikang Zhang; Hongtao Fu; Jun Wang; Dongqi Zhu; Xiuqing Hu; Yunguo Du; Changfei Gou; Chaoliang Wang; Mingfeng Li; Hai Wu (Marine Georesources & Geotechnology, 2021)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

Debris flows originating from colluvium deposits in hollow regions during a heavy storm process in Taining, southeastern China - Yong Zhang; Ningsheng Chen; Mei Liu; Tao Wang; Mingfeng Deng; Kanglin Wu; Binish Raj Khanal (Landslides, 2020)

Rhizobia promote the growth of rice shoots by targeting cell signaling, division and expansion - Qingqing Wu; Xianjun Peng; Mingfeng Yang; Wenpeng Zhang; Frank B. Dazzo; Norman Uphoff; Yuxiang Jing; Shihua Shen (Plant Molecular Biology, 2018)

Scaffold-based design of xanthine as highly potent inhibitors of DPP-IV for improving glucose homeostasis in DIO mice - Yan Ran; Heying Pei; Caifeng Xie; Liang Ma; Yuzhe Wu; Kai Lei; Mingfeng Shao; Minghai Tang; Mingli Xiang; Aihua Peng; Yuquan Wei; Lijuan Chen (Molecular Diversity, 2015)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)